Students' Inductive Reasoning Ability in Solving Fractional Problems Through Contextual Approach - Marwa Astriani Kamsurya; Dede Ngadino (Lembaga Intelektual Muda Maluku, 2024)
Students can think and reason about a math problem if they can understand the math problem. A way of looking at mathematical problems also influences the mindset about the solution to be done. Through a contextual approach, students can practice their thinking skills in solving problems. This study aims to determine the ability of mathematical inductive reasoning with a contextual approach in solving fractional problems. This type of research is descriptive qualitative. The number of subjects in this study was 1 obtained using the Purposive Sampling technique using certain criteria, namely student test results on fractional material. The instruments used are using tests and interviews. Tests are used for the process of determining subjects, and interviews are used to determine inductive reasoning abilities. The interview process used is an unstructured interview and is conducted on subjects, peers, and subject teachers. Data analysis techniques using qualitative analysis consist of data collection, data presentation, and conclusions. The results of data analysis show that subjects in the process of solving problems on fractional material have inductive reasoning abilities in the process of solving problems and meet all indicators of inductive reasoning used in this study, namely observing the pattern of questions given, looking for relationships contained in the questions to facilitate problem solving, and determining the estimation of problem solving and drawing conclusions, and can predict the pattern of solving the next problem